SHM_415564_HST_3D Pottery Rim Fragment in the Pitted Ware Culture/Fagervik III Style - Lernestål, Erik; Myrin, Ola; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Middle Neolithic pottery rim fragment in the Pitted Ware Culture/Fagervik III style collected from Fagervik in Östergötland and held in the collections of the National Historical Museums in Stockholm. Fragment decorated with round impressions.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=669

Link to Sök I Samlingarna

https://samlingar.shm.se/object/49563CC9-94B6-4B21-971C-B0F822C82B15
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; History and archaeology; Archaeology/history; Dynamic Collections; Pitted Ware Culture; Fagervik; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi